Prolyl oligopeptidase-like deficient Trypanosoma evansi parasites are associated with reduced interleukin-10 concentrations in vivo and in vitro. (4th December 2017) - Kangethe, Richard T.; Winger, Eva M.; Settypalli, Tirumala B.K.; Wijewardana, Viskam; Slaets, Johanna; Coetzer, Theresa H. T.; Diallo, Adama
Abstract: The protozoan parasite Trypanosoma evansi is responsible for causing Surra in a variety of mammalian hosts over a wide geographical area. In the absence of an effective vaccine and increasing resistance to current chemotherapeutic agents, peptidases from the S9 prolyl oligopeptidase family have been identified as potential drug and vaccine targets. In order to understand the function of these peptidases during infection, three null mutant clones for prolyl oligopeptidase ( Δpop ), prolyl oligopeptidase-like ( Δpop-like ) and oligopeptidase B ( Δopb ) were generated in T. evansi RoTat 1.2 parasites and used for infection of mice. Mice inoculated with T. evansi Δpop-like mutants were able to survive longer than other groups of mice inoculated with Δpop, Δopb mutants or wild-type parasites. The regression analysis of plasma from mice-infected over time using Δpop-like mutants showed stable levels of interleukin-10 (IL-10) (non-significant slope, P = 0·171) and declining IL-1b levels (negative slope, P = 0·04) when compared with the wild-type control that demonstrated increasing levels of IL-10 and IL-1b ( P < 0·01 for both). Further analysis using mouse spleen cells in an in vitro 24 h incubation assay revealed that the percentage of IL-10 producing CD3 positive cells display significantly lower values when incubated with Δpop-like parasites than the wild-type clone ( P = 0·002). These results suggest that prolyl oligopeptidase-like peptidase may play a role in immune responses during T. evansi infections by affecting interleukin concentrations in the host.